Perspectives of Female Physicians Who Lead in the Public Health Sector in India – A Qualitative Study - Sangeeta Saxena; Elizabeth Tisdell; Betsy Aumiller (Preventive Medicine: Research & Reviews, 2024)
Introduction: This qualitative, research studies female physicians in leadership roles to identify reasons for their underrepresentation. Materials and Methods: Fourteen female physicians in leadership positions in India’s federal and state ministries of health were purposively sampled and interviewed online. Results: Female physician face cultural, organisational and structural barriers. Familial expectations and imbibed, internalised responsibility to prioritise family hold them back. The rigid bureaucracy makes their workplaces non-inclusive. Microaggressions and implicit gender bias abound. A formalised training system and a performance-based reward system are absent. The enabling factors are family support, incidental learning, being emotionally intelligent and passion for their work. Conclusions: Action at the societal, medical education and public health system structural level can motivate female physicians to assume for leadership positions.